Pendekatan Pruralistik Manajemen Kelas Modern dalam Kearifan Lokal: (Pengelolaan Kelas Besar Pembelajaran di Pesantren) - Muhammad ‘Ainul Yaqin (Tarbiyah Departement collaboration with AMCA, 2016)
Pesantren as a base class learning traditional not only reveals the traditional characters alone, but the value nalai keraifan locality pesantren which is equivalent to the concept of learning modern already exist and have been used by actors pesantren, in terms of classroom management of learning, schools are not just looking at the class of the room narrow as pembellajaran classical modern concept, but schools have given more meaning that boarding is itself actually a large classroom where efforts kijaji approach occurs pruralistik.